Studies on Shelf-Life of Some Promising Mango (Mangifera indica L.) Hybrids under Ambient Condition - Karuna, K; Kumar, Mukesh; Mankar, Abhay; Tiwari, Dhiru Kumar; Nirgude , Vishal (Journal of Postharvest Technology, 2014)
Eleven mango hybrids Alfazli, Amrapali, Jawahar, Mahmoodbahar, Mallika, Neeleshan, Neeludin, Prabhashankar, Ratna, Sabri, Sunder Langra and Langra were taken as local check to study their shelf life. The PLW and spoilage of fruit increased with prolongation of storage period, regardless of cultivars. On termination day of storage (15th day) the minimum PLW (18.65%) and spoilage (22.36%) was noted in Mallika while highest PLW (34.85%) and spoilage (58.67%) were obtained in check variety Langra. TSS content in fruits increased up to 12th day and further extension in storage period it declined in all the cultivars. On concluding day of experiment (15th day) the maximum TSS was noted in Mallika (23.02°Brix) while the lowest was obtained inLangra (18.18°Brix). The titratable acidity and ascorbic acid content in fruits decreased progressively upto end of the experiment. On 15th day of storage the maximum titratable acidity was recorded in Mallika (0.346%) while the lowest was obtained in Sabri (0.132%). The highest ascorbic acid produced by Langra (92.86 mg/100g juice) while,the lowest ascorbic acid was noticed in Mahmoodbahar (15.18 mg/100g juice). Total sugar enhanced gradually up to 9th day of storage, except in Mallika which showed increasing trend up to 12th day. On last day of storage the maximum total sugars was noticed in Mallika (14.98%) however, the lowest was recorded in Langra (11.74%). On 12th day of storage Mallika was organoleptically rated as excellent. On last day of storage,Amrapali, Mahmoodbahar, Mallika and Neeludin were fair while rest of the cultivars were under poor grade quality.The keeping quality of Mallika, Alfazli, Ratna and Amrapali were better than other hybrids and check variety Langra.Especially fruits of Mallika can be stored for longer period at ambient conditions.